Scalanie i percepcja wizualna. Kognitywne warunki odbioru dzieł sztuki (malarstwo, rzeźba, literatura) - Saja, Krystian (Przestrzenie Teorii, 2019)
This article aims to indicate universal cognitive diagrams for the process of interpreting and creating works of art. This text deals primarily with issues such as visual perception, neural representations and mental maps. Each of these concepts has a direct connection with the reception of works of art (painting, sculptural and literary). A certain scope of cognitive processes may constitute a cognitive universe with respect to works of visual art. In every field of art, a set of similar, if not identical patterns with regard to a specific realization is noticed. We can therefore speak of generalizations, mutations and emanations in culture. This article is only a research proposal, which requires a wider study.